2019
DOI: 10.1002/jcp.28388
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain noncoding RNA GAS5 mediates oxidative stress in cardiac microvascular endothelial cells injury

Abstract: This study is performed to figure out the role of long‐chain noncoding RNA growth‐arrest specific transcript 5 (GAS5) in homocysteine (HCY)‐induced cardiac microvascular endothelial cells (CMECs) injury. CMECs were cultured and the model of CMECs injury was established by coincubation with HCY. To construct stable overexpression of GAS5 cells, the expression of GAS5, microRNA‐33a‐5p (miR‐33a‐5p) and ATP‐binding cassette transporter A1 (ABCA1), and biological characteristics of cells were determined. The messen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…11 And lncRNA GAS5 can regulate the oxidative stress in the heart. 12 In our study, we implemented high-glucose treatment to NRC and NMC and tested the expression of lncRNA GAS5 in NRC and NMC by qRT-PCR assay. And we found that lncRNA GAS5 expression was increased with the time of high-glucose treatment increasing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 And lncRNA GAS5 can regulate the oxidative stress in the heart. 12 In our study, we implemented high-glucose treatment to NRC and NMC and tested the expression of lncRNA GAS5 in NRC and NMC by qRT-PCR assay. And we found that lncRNA GAS5 expression was increased with the time of high-glucose treatment increasing.…”
Section: Discussionmentioning
confidence: 99%
“…11 And lncRNA GAS5 can regulate oxidative stress in the heart. 12 Here we detected the expression of lncRNA Gas5 in NRC and NMC when treated with 30 mmol/L high glucose via qRT-PCR assay ( Figure 1A). We found the expression of lncRNA GAS5 was upregulated with the hours of 30 mmol/L high-glucose treatment.…”
Section: Tcf3 Could Bind To Gas5 Promoter and Activate The Expressimentioning
confidence: 95%
See 1 more Smart Citation
“…Besides, the increased risk of cardiovascular disease could also be partially attributed to Hhcy ( Borowczyk et al, 2019 ). Its possible underlying mechanism is that elevated serum homocysteine (Hcy) may lead to endothelial dysfunction ( Esse et al, 2019 ; Wu et al, 2019 ; Yan et al, 2019 ), neurotoxicity ( Moretti & Caruso, 2019 ) and up-regulation of thrombosis formation factors ( Diao et al, 2019 ; Jin et al, 2018 ). However, the likelihood of applying Hcy to prognosticate AIS patients’ clinical outcomes after rtPA therapy hasn’t been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…And miR-33a-5p has been proved to inhibit the growth and migration of colorectal cancer by targeting MTHFD2 [13]. MiR-33a-5p also plays a role in cardiovascular diseases, according to Liwei Diao et al [14] increased expression of miR-33a-5p was found in cardiac microvascular endothelial cell injury. Another study [15] found that inhibition of miR-33a could inhibit cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%